Some Motor abilities Level for Students in the First Cycle of Basic Education in Muscat - هشام أحمد مهيب; كاشف زايد نايف; الطوقي منصور بن سلطان; الطواسني مرفت محمد; حمدي محمود وجيه; أحمد الهام عبد المنعم; مرسي هالة علي (Journal of Sport Science Technology and Physical Activities, 2025)
This study assessed the level of some motor abilities for students in the first cycle of basic education (grades I to IV) in Muscat, Sultanate of Oman, aiming to know the level of motor abilities components so that organizers of the physical education and sport can determine the requirements and objectives of the programs offered. The study was conducted on 480 students (male) implementing a group of measurements namely: height, weight, muscle strength (grip right & left hand – legs - back) as well as flexibility of the spine on the horizontal axis, legs explosive power, agility, coordination, static balance and reaction time. The results show significant increase in most students motor abilities except flexibility, and there are variation in the rate of development that emerged clearly at the beginning of the third grade, while the increase of most motor abilities were close between the students in grades III and IV. However, the grip strength showed normal increase among the four grades. The study recommend to designing school sports programs relevance to students' abilities in these grades considering flexibility. In addition, it recommends using the results as a guideline for evaluating students motor abilities development and comparing between Omani male students with female and their peers from other communities as well as conducting studies on other school grades.